2020
DOI: 10.4049/immunohorizons.2000026
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles from Pseudomonas aeruginosa Suppress MHC-Related Molecules in Human Lung Macrophages

Abstract: Pseudomonas aeruginosa, a Gram-negative bacterium, is one of the most common pathogens colonizing the lungs of cystic fibrosis patients. P. aeruginosa secrete extracellular vesicles (EVs) that contain LPS and other virulence factors that modulate the host's innate immune response, leading to an increased local proinflammatory response and reduced pathogen clearance, resulting in chronic infection and ultimately poor patient outcomes. Lung macrophages are the first line of defense in the airway innate immune re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Several mechanisms have been identified including alteration and/or activation of redundant signaling pathways, and downmodulation of the antigen-presenting machinery to evade anti-tumor-specific T cells, all contributing to the resurgence of resistant tumor cells 1 , 4 . In a recent study, TGFβ has been identified as a major player in driving a resistant phenotype and contributing to MHC class I downmodulation in melanoma 35 . We and others have shown that tumor-infiltrating fibroblasts, macrophages, and B-cells have an important role in therapy resistance 2 , 36 , 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been identified including alteration and/or activation of redundant signaling pathways, and downmodulation of the antigen-presenting machinery to evade anti-tumor-specific T cells, all contributing to the resurgence of resistant tumor cells 1 , 4 . In a recent study, TGFβ has been identified as a major player in driving a resistant phenotype and contributing to MHC class I downmodulation in melanoma 35 . We and others have shown that tumor-infiltrating fibroblasts, macrophages, and B-cells have an important role in therapy resistance 2 , 36 , 37 .…”
Section: Discussionmentioning
confidence: 99%
“…A last important point has to be mentioned: cell 1 in Figure 6 A and cell 3 in Figure 7 H were surrounded by material that likely corresponds to excreted vesicles. Such vesicles are the sign of a stressed or not-healthy bacterium [ 49 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…EVs secreted by P. aeruginosa (also known as outer membrane vesicles (OMVs) contain virulence factors, such as peptides, which contribute to biofilm formation, protecting growing bacteria from the host immune response and antibiotic action (Esoda and Kuehn, 2019). Additionally, P. aeruginosa-released EVs downregulate the expression of MHCrelated molecules in pulmonary macrophages, reducing pathogen clearance (Armstrong et al, 2020). Also, EVs released by P. aeruginosa-infected microglia cells diminish cell viability and the expression of the CC-chemokine ligand CCL4 by uninfected microglia cells (Jones et al, 2019).…”
Section: Extracellular Vesicles As Pivotal Players In Biological Processes Extracellular Vesicles In Invader-host Interplay: Prominent Prmentioning
confidence: 99%